2023
DOI: 10.3390/ijms241310883
|View full text |Cite
|
Sign up to set email alerts
|

A Pectate Lyase Gene Plays a Critical Role in Xylem Vascular Development in Arabidopsis

Abstract: As a major component of the plant primary cell wall, structure changes in pectin may affect the formation of the secondary cell wall and lead to serious consequences on plant growth and development. Pectin-modifying enzymes including pectate lyase-like proteins (PLLs) participate in the remodeling of pectin during organogenesis, especially during fruit ripening. In this study, we used Arabidopsis as a model system to identify critical PLL genes that are of particular importance for vascular development. Four P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 55 publications
0
4
0
Order By: Relevance
“…For example, a homolog of Epsin 3, an accessory protein that facilitates vesicle biogenesis, identified in this study could potentially play a role in the deposition and recycling of wall materials at the tube tip, as Epsin 3 was shown to regulate vacuolar and secretory transport through the trans-golgi network in conjunction with another EPSIN protein [41]. Another protein, Pectate lyase 8 (PLL8), likely influences the pectin content as the up or down-regulation of a related family member alters the pectin content and vascular formation in Arabidopsis [37]. Pectin is a component of pollen tube walls, and at the pollen tube tip, it is the sole component [47], and hence, the pectin dynamics are important for growth responses in these cells.…”
Section: Bioinformatic Analysis Of Filtered Putative Picdpk1 Substratesmentioning
confidence: 82%
“…For example, a homolog of Epsin 3, an accessory protein that facilitates vesicle biogenesis, identified in this study could potentially play a role in the deposition and recycling of wall materials at the tube tip, as Epsin 3 was shown to regulate vacuolar and secretory transport through the trans-golgi network in conjunction with another EPSIN protein [41]. Another protein, Pectate lyase 8 (PLL8), likely influences the pectin content as the up or down-regulation of a related family member alters the pectin content and vascular formation in Arabidopsis [37]. Pectin is a component of pollen tube walls, and at the pollen tube tip, it is the sole component [47], and hence, the pectin dynamics are important for growth responses in these cells.…”
Section: Bioinformatic Analysis Of Filtered Putative Picdpk1 Substratesmentioning
confidence: 82%
“…Notably, FaPL5 was clustered with AtPLL19 in Group I, which is different from the other six ripening related FaPLs (Figure 2). AtPLL19 was identified by its xylem-specific expression in Arabidopsis [32]. Combined with the fact that FaPL5 had the lowest expression among the seven ripening related FaPLs (Figure 5B), it can be speculated that FaPL5 may mainly function in xylem vascular development rather than fruit softening, which needs further research.…”
Section: Discussionmentioning
confidence: 98%
“…Collectively, the transcriptional co-regulation between AtRZF1 and RGL1 plays an important in the osmotic stress response through the Pro biosynthesis and cell wall pectin composition-mediated pathway. Bai et al (2023) reported that pectate lyase may directly impact the cell wall integrity pathway, thereby influencing the components of the cell wall and ultimately driving the development of the xylem and phloem. In mature inflorescence stems of Arabidopsis, xylem cells typically maintain six to eight vascular bundles (Turner & Somerville, 1997).…”
Section: Discussionmentioning
confidence: 99%
“…Recent reports have shown that the Pectate Lyase-Like (PLL) protein, which is an enzyme that breaks down pectin, affects root growth, soluble sugar levels, and vascular development in Arabidopsis (Bai et al, 2023;Sun & Nocker, 2010). As the transcript levels of RGL1 affect pectin contents and primary root elongation, we investigated the influence of RGL1 expression levels on vascular development in plant inflorescence stems.…”
Section: Reduced Expression Of Rgl1 Affects Vascular Tissue Developmentmentioning
confidence: 99%